2002
DOI: 10.1007/s11661-002-0124-3
|View full text |Cite
|
Sign up to set email alerts
|

Parameters controlling microstructure and hardness during friction-stir welding of precipitation-hardenable aluminum alloy 6063

Abstract: The aluminum (Al) alloys 6063-T5 and T4 were friction-stir welded at different tool rotation speeds (R), and then distributions of the microstructure and hardness were examined in these welds. The maximum temperature of the welding thermal cycle rose with increasing R values. The recrystallized grain size of the weld increased exponentially with increasing maximum temperature. The relationship between the grain size and the maximum temperature satisfied the static grain-growth equation. In the as-welded condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
253
0
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 425 publications
(279 citation statements)
references
References 39 publications
23
253
0
3
Order By: Relevance
“…The heating experiment of Rhodes et al [19] following FSP and the use of static grain growth model to estimate the grain size observed after FSP by Sato et al, [16] Robson and Campbell, [28] and Kumar et al [29] supports the above idea. There are primarily three ways by which grain size development during FSP has been controlled: (1) cooling rate control, (2) peak temperature control, and (3) use of thermally resistant precipitates/dispersoids.…”
Section: A Grain Refinement and The Role Of Al 3 (Sc Zr) Dispersoidsmentioning
confidence: 79%
See 2 more Smart Citations
“…The heating experiment of Rhodes et al [19] following FSP and the use of static grain growth model to estimate the grain size observed after FSP by Sato et al, [16] Robson and Campbell, [28] and Kumar et al [29] supports the above idea. There are primarily three ways by which grain size development during FSP has been controlled: (1) cooling rate control, (2) peak temperature control, and (3) use of thermally resistant precipitates/dispersoids.…”
Section: A Grain Refinement and The Role Of Al 3 (Sc Zr) Dispersoidsmentioning
confidence: 79%
“…Of late, there have been some efforts to obtain UFG microstructure by changing the processing parameters such as tool rotational rate (x) at constant tool traverse velocity (m) or the ratio x/m. [12,16,17] Su et al [18] and Rhodes et al [19] demonstrated the possibility of achieving grains as small as 25 to 100 nm by employing special cooling arrangement during FSP. But as mentioned earlier, most of the mean grain sizes tabulated by Mishra and Ma were larger than 1 lm under ordinary processing conditions.…”
Section: Easy Accessibility Of An Ultrafine-grained (Ufg)mentioning
confidence: 99%
See 1 more Smart Citation
“…Modeling results indicate that the nugget/SZ material has experienced large plastic strains at strain rates in the range 10 1 -10 2 s À1 [8]. Peak temperatures in this region are thought to be in the range from 0.6 to 0.95T Melt , depending on the material, tool design and operating conditions, and the upper portions of this region experience heating and deformation effects from the tool shoulder as well as from the tool pin [14][15][16]. Next is the thermomechanically affected zone (TMAZ), where the material experiences lesser strains and strain rates as well as lower peak temperatures.…”
Section: Transients and Gradients During Fsw/pmentioning
confidence: 99%
“…In this study, the formation of sub-micron and nano-scale crystalline structures reflects a direct transformation by coarsening of the highly refined microband structures formed around the tool pin. It should be noted that several recrystallization theories including continuous dynamic recrystallization, discontinuous dynamic recrystallization, geometric dynamic recrystallization and recrystallization via particle stimulated nucleation, which were developed to account for grain size control during conventional thermo-mechanical processing, have also been used to explain the formation of fine grain structures (usually 1-10 m) during FSW/FSP [5,[41][42][43][44][45][46][47][48]. Common FSW and FSP technologies inherently involve severe plastic deformation (SPD) as well as transients and gradients in strain, strain rate and temperature.…”
Section: Microstructure Evolutionmentioning
confidence: 99%